Pengaruh Penerapan Ayah ASI (Breastfeeding-Father) terhadap Produksi dan Pengeluaran ASI pada Ibu Postpartum - Thatit Nurmawati; Nawang Wulandari; Ulfa Husnul Fata (STIKes Patria Husada Blitar, 2014)
Cholesterol is needed to stabilize the double layer ( bilayer ) of phospholipids in the membrane . Cholesterol is also a precursor of steroid hormones . High cholesterol levels can cause need to watch out for deep vein thrombosis , especially when high LDL levels . Control of cholesterol in the body is absolutely necessary to regulate the levels of fat consumed each day . Carrots ( Daucus Carota ) as a source of fiber and antioxidants ( carotenoids , polyphenols and vitamin C ) that contribute to protection against cardiovascular disease . Raw carrots have tough cell walls so that less than 25 % of beta - carotene is converted to vitamin A. However, the cooking process can dissolve cellulose by breaking down the cell wall so as to facilitate absorption . The purpose of research to determine the speed difference between the cholesterol-lowering treatment with ripe raw carrots .This study used a true experimental design with control. White rat ( Rattus norvegicus ) were given a high cholesterol diet is used as experimental animals were divided into a control group and the treatment group . The treatment group were treated raw and cooked carrots . Simvastatin for the control group . Incubation 8 weeks to determine changes in cholesterol levels . Data were analyzed using parametric statistical test Kruskal Wallis test .The results showed no differences at all cholesterol-lowering treatment . Allegedly content of Î² -carotene in carrots is low . In a variety of carotenoid compounds , Î² -carotene will have lower antioxidant activity . Pectin also suffered damage to the heating activity . It is necessary to further test of the difference in the treatment of raw and cooked